The Efficacy of Selected Desensitizing OTC Products: A Systematic Review. (27th March 2014) - Talioti, E.; Hill, R.; Gillam, D. G.
Abstract : Objectives . The aim of the present study was to review the published literature in order to identify relevant studies for inclusion and to determine whether there was any evidence on the clinical effectiveness of selected desensitizing toothpastes, calcium sodium phosphosilicate (CSPS), amorphous calcium phosphate (ACP), nanohydroxyapatite, and casein phosphopeptide-amorphous calcium phosphate (tooth mousse) on reducing dentine hypersensitivity (DH). Materials and Methods . Following a review of 593 papers identified from searching both electronic databases (PUBMED) and hand searching of relevant written journals, only 5 papers were accepted for inclusion. Results . Analysis of the included studies (3 CSPS and 2 ACP) would suggest that there may be some benefit for patients using these products for reducing DH. No direct comparative studies were available to assess all these products under the same conditions neither were there any comparative randomised controlled studies that compared at least two of these products in determining their effectiveness in treating DH. Conclusions . Due to the small number of included studies, there are limited clinical data to support any claims of clinical efficacy of these OTC products. Further studies are therefore required to determine the efficacy of these products in well-controlled RCT studies with a larger sample size.